2021
DOI: 10.1097/aud.0000000000001002
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Allocate Our Resources When Listening and Memorizing Speech in Noise? A Pupillometry Study

Abstract: Objectives: Actively following a conversation can be demanding and limited cognitive resources must be allocated to the processing of speech, retaining and encoding the perceived content, and preparing an answer. The aim of the present study was to disentangle the allocation of effort into the effort required for listening (listening effort) and the effort required for retention (memory effort) by means of pupil dilation. Design: Twenty-five normal-hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 55 publications
(131 reference statements)
7
39
0
Order By: Relevance
“…This finding is in line with our previous study performed on a group of NH listeners in quiet versus 4T conditions without any reverberation [20]. Consistent with the findings of Beatty and Kahneman (1966) [19] and Bönitz et al (2021) [21], the increasing trend in sentence baseline can be interpreted as increasing memory effort. In addition to the relative baseline correction used in this study, the latter study [21] analyzed the intercept and slope of sentence baseline and sentence dilation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is in line with our previous study performed on a group of NH listeners in quiet versus 4T conditions without any reverberation [20]. Consistent with the findings of Beatty and Kahneman (1966) [19] and Bönitz et al (2021) [21], the increasing trend in sentence baseline can be interpreted as increasing memory effort. In addition to the relative baseline correction used in this study, the latter study [21] analyzed the intercept and slope of sentence baseline and sentence dilation.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings of Beatty and Kahneman (1966) [19] and Bönitz et al (2021) [21], the increasing trend in sentence baseline can be interpreted as increasing memory effort. In addition to the relative baseline correction used in this study, the latter study [21] analyzed the intercept and slope of sentence baseline and sentence dilation. The authors concluded that changes in baseline may reflect the participants' expectation about test difficulty even before the task was given.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Several measures have been used to capture the effects of adverse listening conditions and task demands on resource allocation ( Peelle 2018 ). In the current study, we combined the Sentence-Final Word Identification and Recall (SWIR) test ( Ng et al 2013 , 2015 ; Micula et al 2020 ) with pupillometry ( Wendt et al 2017 ; Ohlenforst et al 2018 ; Zhang et al 2021 ; Bönitz et al 2021 ), which are described individually in the following sections.…”
Section: Introductionmentioning
confidence: 99%
“… Bönitz et al (2021 ) have conducted a study combining pupillometry and a version of the SWIR test in German with lists of three and six sentences in a background noise of four-talker (4T) babble at high speech intelligibility levels. They included older participants with normal hearing.…”
Section: Introductionmentioning
confidence: 99%